Effect of Typha capensis crude rhizome extract on LNCaP prostate cancer cell line - Ilfergane , Abdulkarem A.; Muttardi , Farag A.; Attia, Fathi A. (Journal of Pure & Applied Sciences, 2021)
Typha capensis, commonly referred to as one of indigenous medicinal plants that are traditionally used to treat male fertility problems and various other ailments. Previous studies revealed that T. capensis has indeed a beneficial effect on male reproductive functions and aging male symptoms. LNCaP cells incubated with different concentrations of crude aqueous extract of T. capensis rhizomes (0.01, 0.02, 0.1, 1, 10 and 100 μg/ml) and control (without extract) for 24 and 96 hours, after incubation. The following parameters were evaluated: cell morphology and viability (determined by means of MTT assay). LNCaP cells showed a decline in cell viability at the incubation period 96 hours (-82.4%) more than 24 hours (-64.7%) indicating more cell death. cell early apoptosis (determined by means of Annexin V-Cy3 binding), DNA fragmentation (determined by means of the TUNEL assay). After 96 hours of exposure, all concentrations caused a dose-dependent increase in early apoptosis in the cells. At higher concentrations (10 and 100 μg/ml), a significant increase of 38.8% (P=0.009) and 52.3%(P<0.001), respectively, in the percentage of cells with signs of early apoptosis was significant. a significant increase of TUNEL-positive cells was found between the control and 1, 10, 100 μg/ml.